1993
DOI: 10.1177/0143034393141006
|View full text |Cite
|
Sign up to set email alerts
|

Self-Modeling with Preschoolers

Abstract: A complex reversal design was used to investigate the effectiveness of self-modeling procedures in reducing aggression and noncompliance in six preschool-age children. Self-modeling was compared with peer modeling and a control condition over a ten-week period. Follow-up and maintenance of behavior change was studied, as was generalization. No positive effects were found for the selfmodeling intervention in reducing instances of aggression or noncompliance. Supplementary analysis of four subjects' data further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 4 publications
2
22
0
Order By: Relevance
“…With the exception of John, the positive TRS ratings did not generalize to the home setting as reflected in the BASC-2 PRS ratings. These inconsistent results comport with previous research examining the efficacy of VSM technologies with individuals diagnosed with emotional and behavioral disorders (e.g., Clark et al 1993;Mason et al 2012;Possell et al 1999). Although the overall implication of these findings should be interpreted cautiously given the relatively small sample sizes that have been employed, it is certainly possible that younger children with behavioral and emotional disorders may have difficulty processing information presented through visual technologies such as VSM in a way that facilitates generalization across settings.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…With the exception of John, the positive TRS ratings did not generalize to the home setting as reflected in the BASC-2 PRS ratings. These inconsistent results comport with previous research examining the efficacy of VSM technologies with individuals diagnosed with emotional and behavioral disorders (e.g., Clark et al 1993;Mason et al 2012;Possell et al 1999). Although the overall implication of these findings should be interpreted cautiously given the relatively small sample sizes that have been employed, it is certainly possible that younger children with behavioral and emotional disorders may have difficulty processing information presented through visual technologies such as VSM in a way that facilitates generalization across settings.…”
Section: Discussionsupporting
confidence: 53%
“…Buggey (2009) stated that longer video lengths produced negligible improvements in comparison to shorter video clips. Clark et al (1993) also found no significant improvements when targeting behavior using VSM with a sample of male preschool students (N=6) diagnosed with oppositional defiant disorder. Each student participated in three conditions which included the following: self-modeling, peer modeling, and a control condition.…”
Section: Clinical Applications Of Vsmmentioning
confidence: 85%
“…The second study with negative findings also targeted aggressive and noncompliant behaviors (Clark et al, 1993). In this study, no substantial reduction in negative behaviors occurred after the introduction of VSM.…”
mentioning
confidence: 76%
“…It is interesting that two studies were found in which selfmodeling was found to be ineffective, and both of these had preschoolers as participants. Clark et al (1993) found that selfmodeling did not modify aggressive behaviors in a group of six preschoolers who were labeled as oppositional-defiant. Buggey (1995b) had mixed results in a study aimed at training language skills to two preschoolers: One child made significant gains in mean length of utterance and intelligibility, whereas the second child made no measurable gains in his target behaviors.…”
mentioning
confidence: 87%